Efeito do extrato bruto das folhas de Echinodorus Macrophyllus e de frações semipurificadas sobre a função renal em ratos com necrose tubular aguda induzida por gentamicina - Gustavo Pereira Cosenza (2010)
The Echinodorus macrophyllus (E. macrophyllus), Alismatacea family, is a native specie to Brazil where he is known for leather hat, tea mineiro and herb swamp. The aim of this study was to evaluate the possible effect of the crude extract of the leaves of E. macrophyllus (EB) and it extracted fractions (FAE, FB e FAq) on renal function in normal rat and rat with acute tubular necrosis (ATN) induced by gentamicin (GT). EB, obtained by percolation, was submitted to extraction with ethyl acetate, yielding a fraction rich in flavonoids (FAE). Then, the remainingaqueous fraction was extracted with n-butanol resulting in the butanol fraction (FB). The remaining aqueous fraction was named FAq. Diuresis was assessed in male Wistar rats, normal (250-350g). The rats were volume-expanded (4% of body weight) with 0.9% NaCl in the absence (control) and presence of varying doses (10-1000 mg / kg) of EB, FAE, FB e FAq. Then the rats were placed individually in metabolic cages. The urine volume was measured every 30 min for 3 h (180 min). To evaluate the effect of EB, FB and FAq on renal function, were used 8 groups ofrats were 4 groups consisting of normal rats (Sal Sal,Sal EB, Sal FAE e Sal FB) and 4 rats with ATN (GT Sal, GT EB, GT FAE e GT FB). The experiment was divided into three periods: aclimatation (ACL), induction of NTA (Sal or GT) and treatment (EB, FB or FAE). After the ACL, the NTA was or not (with saline) induced with GT, for five days. After this period, both normal rat and those rat with ATN were treated or not (with saline) by gavage, with EB, FB or FAE for 7 days. Urine and plasma were collected at the end of the ACL at the end of the induction of NTA and 4 and 7 days of treatment. In the chromatographic profile of EB, FB and FAEshowed the presence of several flavonoids (vitexin, isovitexin and orientin). The results showed that tea may have an ambiguous action on diuresis (it increases and decreases). EB already exerted an antidiuretic action especially at a dose of 300 and 1000 mg/kg. Although no prominent effect in normal rats, rats with ATN, EB reversed the increase in plasma creatinine and the reduction of GFR and fractional excretion of sodium and potassium. The FB, although it has not affected the glomerular filtration rate also decreased the fractional excretion of electrolytes. This suggests that the decrease in this excretion observed in response to EB may be due to the FB fraction that is rich in saponins, but also has flavonoids. As the FAE the fraction richer in flavonoids than FB and did not interfere with the excretion of sodium and potassium, it can be suggested that this effect was due to the saponins present in the FB. In summary, our results show that under the conditions used by us, although E. macrophyllus did not induce the expected effect ondiuresis, it was effective in improving glomerular function that was affected by GT. The EB also seems to have a beneficial effect tubular as it was able to reduce the excretion of sodium and potassium was elevated in response to GT. This tubular effect may be caused by substances (such as saponins) found in the FB.